Ethylene regulates auxin-mediated root gravitropic machinery and controls root angle in cereal crops - Kong, Xiuzhen; Xiong, Yali; Song, Xiaoyun; Wadey, Samuel; Yu, Suhang; Rao, Jinliang; Lale, Aneesh; Lombardi, Marco; Fusi, Riccardo; Bhosale, Rahul; Huang, Guoqiang (Plant physiology (Bethesda), 2024)
Abstract Root angle is a critical factor in optimizing the acquisition of essential resources from different soil depths. The regulation of root angle relies on the auxin-mediated root gravitropism machinery. While the influence of ethylene on auxin levels is known, its specific role in governing root gravitropism and angle remains uncertain, particularly when Arabidopsis (Arabidopsis thaliana) core ethylene signaling mutants show no gravitropic defects. Our research, focusing on rice (Oryza sativa L.) and maize (Zea mays), clearly reveals the involvement of ethylene in root angle regulation in cereal crops through the modulation of auxin biosynthesis and the root gravitropism machinery. We elucidated the molecular components by which ethylene exerts its regulatory effect on auxin biosynthesis to control root gravitropism machinery. The ethylene-insensitive mutants ethylene insensitive2 (osein2) and ethylene insensitive like1 (oseil1), exhibited substantially shallower crown root angle compared to the wild type. Gravitropism assays revealed reduced root gravitropic response in these mutants. Hormone profiling analysis confirmed decreased auxin levels in the root tips of the osein2 mutant, and exogenous auxin (NAA) application rescued root gravitropism in both ethylene-insensitive mutants. Additionally, the auxin biosynthetic mutant mao hu zi10 (mhz10)/tryptophan aminotransferase2 (ostar2) showed impaired gravitropic response and shallow crown root angle phenotypes. Similarly, maize ethylene-insensitive mutants (zmein2) exhibited defective gravitropism and root angle phenotypes. In conclusion, our study highlights that ethylene controls the auxin-dependent root gravitropism machinery to regulate root angle in rice and maize, revealing a functional divergence in ethylene signaling between Arabidopsis and cereal crops. These findings contribute to a better understanding of root angle regulation and have implications for improving resource acquisition in agricultural systems.Ethylene regulates root angle in rice and maize by modulating auxin biosynthesis.